Between Science, Art, and Life: didactics as a responsive act - Patrícia Corsino (Universidade Federal do Rio Grande do Sul, 2015)
This essay aims to bring reflections to think the didactics understood as a responsive act, a concept coined by Mikhail Bakhtin that implies acting as a responsible response provided by the subject that faces him in with the otherness. Initially, it develops the concepts present in the title. It claims that the self is constituted in the relation to the other. The didactics is a responsible answer, not indifferent to the subjects to whom the teaching is aimed at. According to this perspective, principles for the didatics are presented. The theoretical framework supporting the arguments of the essay includes the studies of Bakhtin, Arendt, Benjamin, Charlot, Vigotski, among others.